If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6yx + -12x = 0 Reorder the terms: -12x + 6xy = 0 Solving -12x + 6xy = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), '6x'. 6x(-2 + y) = 0 Ignore the factor 6.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-2 + y)' equal to zero and attempt to solve: Simplifying -2 + y = 0 Solving -2 + y = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + y = 0 + 2 Combine like terms: -2 + 2 = 0 0 + y = 0 + 2 y = 0 + 2 Combine like terms: 0 + 2 = 2 y = 2 Add '-1y' to each side of the equation. y + -1y = 2 + -1y Combine like terms: y + -1y = 0 0 = 2 + -1y Simplifying 0 = 2 + -1y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
x = {0}
| k=0,1,2,1/2,-1-2 | | --8=4x/9 | | 0=-16x^2+90x | | 5=.1*x | | 44/8= | | 4.8=.9*x | | y=-16+90 | | -5/12y≤25 | | 40-5x+7=0 | | 2w^2+5w+3=0 | | 4x+6=2(x+7) | | 2x^3-x^2-10x-7=0 | | -3(6-x)-3=x-4 | | 8(x+3)=8x+2x | | 9x-1=4x | | (9/2)/8=n/4 | | 14+3(y+4)-2y= | | (12a^3b^2-6a^2b-24ab^2)/(6ab) | | X^2+21=11x-3 | | x^2+y^2-10x+10y=0 | | 1/4(x-9)1/15(4x-1) | | x^2+y^2=124 | | log(2x+5)-log(x-4)=1 | | 36s-28s-63= | | 5-(3-x)=x | | 8-3x=20-5x | | 1/3(x-10)1/8(3x-1) | | 14+3(y+4)-2= | | 15-ln(4-x)=0 | | 1/3(x-4)1/8(3x-1) | | f(x)=2x^3-2 | | 1/2(x-90)1/3(2x-1) |